Behind the veil: the strategic use of religious garb - Aksoy, O; Gambetta, D (Oxford University Press, 2016)
There is anecdotal evidence that since the late 20th century young, educated, and urban Muslim women veil more frequently and strictly. Does this imply that the classical sociological theories of religion, which predict that modernization should cause a decrease in religious behaviours, do not apply to Islam? We investigate this question using structural equation modelling to analyse three datasets, one from Turkey, one covering 25 Muslim countries, and one from Belgium where Muslims are a minority. We find that averagely religious women conform to the classical theories’ predictions. But among highly religious women the modernizing forces—education, occupation and higher income, urban living, and contacts with non-Muslims—increase veiling. We conjecture that for highly religious women modernizing factors raise the risk and temptation in women's environments that imperil their reputation for modesty: veiling would then be a strategic response, a form either of commitment to prevent the breach of religious norms or of signalling women’s piety to their communities. Our findings have implications for cultural policy and Muslim integration in Europe.